A landscape of shifting identities amid urban invasion: Tamara Duda’s novel Daughter through a translation lens - Antonova, Anna (Studia Rossica Posnaniensia, 2024)
In the environment of Russia’s ongoing war against Ukraine, literary translation acquires critical significance as a way to get Ukraine’s narratives of destruction and urbicide across cultural and political borders. This article will focus on Daisy Gibbons’s 2021 translation of Tamara Duda’s 2019 novel Daughter, set in the Eastern Ukrainian city of Donetsk, to examine the translator’s project of reconstructing the complex interplay of Eastern and Western Ukrainian identities embroiled in the narrative of crawling occupation. Daughter tells the story of Russia’s 2014 invasion of Donetsk, dissecting the city’s fragmented identity along cultural and linguistic divides and exploring internal tensions and propaganda-fueled conflicts leading to its eventual downfall. The storyline adopts the female protagonist’s insider/outsider perspective, tracing her gradual evolution from an invisible observer to a fearless insurgent fighting for the survival of her unravelling home. The analysis will centre on the translator’s approach, which combines textual and paratextual techniques to highlight the processes of division and destruction – with their transformative impact on the urban space – and to enter into a visible dialogue with the narrator/protagonist’s voice to amplify and reinforce its distinctly pro-Ukrainian perspective.